The Pleiotropic Effects of Vitamin D in Gynaecological and Obstetric Diseases: An Overview on a Hot Topic. (27th April 2015) - Colonese, Francesca; Laganà, Antonio Simone; Colonese, Elisabetta; Sofo, Vincenza; Salmeri, Francesca Maria; Granese, Roberta; Triolo, Onofrio
Abstract : The traditionally recognized role of vitamin D consists in the regulation of bone metabolism and calcium-phosphorus homeostasis but recently a lot of in vitro and in vivo studies recognized several "noncalcemic" effects of vitamin D metabolites. Accumulating evidence suggests that the metabolic pathways of this vitamin may play a key role in the developing of gynaecological/obstetric diseases. VDR-mediated signalling pathways and vitamin D levels seem to (deeply) affect the risk of several gynaecological diseases, such as polycystic ovary syndrome (PCOS), endometriosis, and ovarian and even breast cancer. On the other hand, since also the maternal-fetal unit is under the influence of vitamin D, a breakdown in its homeostasis may underlie infertility, preeclampsia, and gestational diabetes mellitus (GDM). According to our literature review, the relationship between vitamin D and gynaecological/obstetric diseases must be replicated in future studies which could clarify the molecular machineries behind their development. We suggest that further investigation should take into account the different serum levels of this vitamin, the several actions which arise from the binding between it and its receptor (taking into account its possible polymorphism), and finally the interplay between vitamin D metabolism and other hormonal and metabolic pathways.